2010
DOI: 10.1371/journal.pone.0010256
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Quasispecies of Pandemic 2009 Influenza A Virus (A/H1N1/2009) by De Novo Sequencing Using a Next-Generation DNA Sequencer

Abstract: Pandemic 2009 influenza A virus (A/H1N1/2009) has emerged globally. In this study, we performed a comprehensive detection of potential pathogens by de novo sequencing using a next-generation DNA sequencer on total RNAs extracted from an autopsy lung of a patient who died of viral pneumonia with A/H1N1/2009. Among a total of 9.4×106 40-mer short reads, more than 98% appeared to be human, while 0.85% were identified as A/H1N1/2009 (A/Nagano/RC1-L/2009(H1N1)). Suspected bacterial reads such as Streptococcus pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 30 publications
(39 reference statements)
6
88
0
Order By: Relevance
“…When the sequences were translated to amino acids, the substitution from aspartic acid (D) to glycine (G) (D222G) was a major clone, whereas the substitution from aspartic acid (D) to asparagine (N) (D222N) was a minor clone in the lung. This was consistent with the results of our previous analysis in frozen lung tissues using de novo sequencing with a next-generation DNA sequencer, 29 an effective analytical tool, which needs a high number of copies of viral RNA for analysis. In this study, using formalin-fixed and paraffin-embedded specimens, and a direct sequencing method, we also detected different 2009 H1N1 virus clones with different nucleic acids in the tracheal sample from case 1 (Figure 4), where the D222G substitution was a minor clone and 222D was a major clone.…”
Section: D222g Substitutions In the Hemagglutinin Of 2009 H1n1 Virussupporting
confidence: 92%
“…When the sequences were translated to amino acids, the substitution from aspartic acid (D) to glycine (G) (D222G) was a major clone, whereas the substitution from aspartic acid (D) to asparagine (N) (D222N) was a minor clone in the lung. This was consistent with the results of our previous analysis in frozen lung tissues using de novo sequencing with a next-generation DNA sequencer, 29 an effective analytical tool, which needs a high number of copies of viral RNA for analysis. In this study, using formalin-fixed and paraffin-embedded specimens, and a direct sequencing method, we also detected different 2009 H1N1 virus clones with different nucleic acids in the tracheal sample from case 1 (Figure 4), where the D222G substitution was a minor clone and 222D was a major clone.…”
Section: D222g Substitutions In the Hemagglutinin Of 2009 H1n1 Virussupporting
confidence: 92%
“…This approach has been previously used to resolve genomic sequences of influenza virus [6]; for example, Greninger et al reported that de novo assembled contigs had 90.3% coverage using 60bp short-reads [5], which is in accordance with our results (Table 2). Given the short length of the influenza genome and the structural simplicity of their genes, as compared with most mammal genes, the number of reads covering the target sequence is the most important factor for the success of this approach rather than the election of the The sequencing run generated 20x10 6 paired-end reads, 90bp.…”
Section: Discussionsupporting
confidence: 91%
“…Our results (Table 1) and also previously published studies [6,7] show that direct RNA sequencing can provide very high coverage of the viral genome; however, there can be clinical samples where the number of virus-matching reads is low [29] and pre-amplification is still an option that may need consideration. The selection of the sequencing platform will determine the number of reads that can be obtained.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The majority of A/H1N1pdm09 clones in the frozen lung tissue of case 2009 reportedly harbored the D222G mutation, which enables the virus to infect alveolar epithelial cells (11). We reexamined the HA gene sequence of the 10 A/H1N1pdm09 clones from the FFPE lung sections of case 2009 and noted that 9 of the 10 clones harbored the D222G mutation (Fig.…”
mentioning
confidence: 99%